2007
DOI: 10.1021/ic701636h
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Troilite

Abstract: Low-temperature synthetic pathways can result in crystallization of metastable materials. These methods have been widely explored for the preparation of metal oxides. Adaptation of nonhydrolytic sol-gel chemistry to non-oxide systems offers an elegant route to transition-metal sulfides. The method can be exploited for the facile and reproducible synthesis of iron sulfide crystallizing in the troilite structure. This phase is only found in meteorites and planets and has previously been obtained by high-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Variable temperature diffraction experiments revealed that the troilite phase transformed to monoclinic pyrrhotite of composition Fe 7 S 8 above 250 °C, as evidenced by peak shape analysis of specific reflections. This confirmed that the samples indeed consisted of troilite with an unusual stoichometry, and that NHSG chemistry provides facile access to small, well-defined hexagonal particles of this phase (Figure 6) [116]. …”
Section: Non-hydrolytic Sol-gel Synthesis Of Metal Sulfidesmentioning
confidence: 61%
“…Variable temperature diffraction experiments revealed that the troilite phase transformed to monoclinic pyrrhotite of composition Fe 7 S 8 above 250 °C, as evidenced by peak shape analysis of specific reflections. This confirmed that the samples indeed consisted of troilite with an unusual stoichometry, and that NHSG chemistry provides facile access to small, well-defined hexagonal particles of this phase (Figure 6) [116]. …”
Section: Non-hydrolytic Sol-gel Synthesis Of Metal Sulfidesmentioning
confidence: 61%
“…The pattern of the film grown at 658 K (Figure 4(a)) reveals the formation of both Troilite-2H (FeS; JCPDS 00-037-0477) and Pyrite (FeS 2 ; JCPDS 00-042-1340). The FeS crystalline structure corresponds to hexagonal Troilite-2H [38][39][40] and the FeS 2 corresponds to cubic pyrite. [12,41,42] As the reaction temperature is increased to 768 K (Figure 4(b)), only Troilite is detected indicating that at these reaction temperatures its Downloaded by [University of Sherbrooke] at 01:30 13 April 2015 formation is favored.…”
Section: Resultsmentioning
confidence: 99%
“…Limiting the attention to wet chemistry approaches, a wide plethora of synthetic routes has been proposed in the literature to prepare metal sulphide colloids ranging from non-aqueous sol-gel routes [70][71][72][73], hydro/solvothermal [24,[74][75][76][77][78][79][80][81][82][83][84][85][86], to sono- [19, and radiochemistry [111][112][113][114][115][116][117], laser ablation [118,119], micro- [120][121][122][123][124][125][126][127][128][129][130] and miniemulsion synthesis [131][132][133][134][135][136][137][138], seeded-growth [139] and nucleation/g...…”
Section: Transition Metal Sulphides: Analogies and Differences With Rmentioning
confidence: 99%